Comparison of three infertility-specific measures in men and women going through assisted reproductive technology treatment. (May 2019) - Pedro, Juliana; Frederiksen, Yoon; Schmidt, Lone; Ingerslev, Hans J; Zachariae, Robert; Martins, Mariana V
We compared the psychometric properties of COMPI Fertility Problem Stress Scales, Fertility Problem Inventory, and Fertility Quality of Life Tool in 293 patients enrolled for assisted reproductive technology. COMPI Fertility Problem Stress Scales and Fertility Problem Inventory subscales presented higher internal consistency. COMPI Fertility Problem Stress Scales differentiated best between its domains. Fertility Problem Inventory revealed better concurrent validity. Fertility Quality of Life Tool presented better fit. While discrimination for depression was similar between measures, Fertility Quality of Life Tool was better at discriminating anxiety. Results suggest that while all compared measures are reliable and valid in assessing the psychosocial adjustment to infertility, the choice of measure should be based according to the assessment goals.